Modifiable risk factors of peripheral artery disease and prevention in nursing practice - Ptašinskienė, Diana; Spirgienė, Lina (Slauga. Mokslas ir praktika, 2021)
Peripheral arterial disease (PAD) in the legs or lower extremities is the narrowing or blockage of the vessels that carry blood from the heart to the legs. It is primarily caused by the build-up of fatty plaque in the arteries, which is called atherosclerosis. PAD can happen in any blood vessel, but it is more common in the legs than the arms. Modifiable risk factors for PAD include smoking, hyperlipidemia, hypertension, diabetes. Smoking cessation, controlling elevated blood pressure and blood glucose, losing excess body fat, exercise, proper diet are crucial first steps in the management of the PAD patient for nurses.
Keywords: peripheral artery disease; patients; prevention; nursing practice